Interface‐Induced Pseudocapacitance in Nonporous Heterogeneous Particles for High Volumetric Sodium Storage - Zhao, Bo; Liu, Qianqian; Chen, Yujie; Liu, Qian; Yu, Qian; Wu, Hao Bin (Advanced functional materials, 2020)
Developing pseudocapacitive materials for electrochemical energy storage generally relies on the formation of nanosize and/or nanoporous particles with short solid‐state diffusion distance and high surface area, which leads to low volumetric capacity and severe parasitic reactions. In this work, nonporous bulky heterogeneous particles composed of TiO2 matrix and phosphorus are reported for high volumetric pseudocapacitive Na storage. An in situ formed 3D titanium phosphate interphase serves as a fast ionic transport network, allowing rapid sodiation/desodiation processes within the particles. Such nonporous heterogeneous particles exhibit “interface‐induced pseudocapacitance” with an enhanced volumetric capacity, which is over 50% higher than that of commercial hard carbon anodes. This study demonstrates heterogeneous particles with a well‐engineered nanostructure as a new paradigm for electrode materials design. Nonporous bulky heterogeneous particles composed of a TiO2 matrix and phosphorus are reported for high volumetric pseudocapacitive Na storage. An in situ formed 3D titanium phosphate interphase serves as a fast ionic transport network, allowing rapid sodiation/desodiation processes within the particles. Such “interface‐induced pseudocapacitance” in nonporous particles leads to enhanced volumetric capacity.